2022
DOI: 10.3390/s23010029
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbed Oxygen Ions and Oxygen Vacancies: Their Concentration and Distribution in Metal Oxide Chemical Sensors and Influencing Role in Sensitivity and Sensing Mechanisms

Abstract: Oxidation reactions on semiconducting metal oxide (SMOs) surfaces have been extensively worked on in catalysis, fuel cells, and sensors. SMOs engage powerfully in energy-related applications such as batteries, supercapacitors, solid oxide fuel cells (SOFCs), and sensors. A deep understanding of SMO surface and oxygen interactions and defect engineering has become significant because all of the above-mentioned applications are based on the adsorption/absorption and consumption/transportation of adsorbed (physis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 96 publications
1
14
0
Order By: Relevance
“…Ciftyurek et al reported exceptionally high gas sensing characteristics due to oxygen gas rapidly adsorbing on single and double-charged oxygen vacancy defect sites created by the presence of lower oxidation state of the metal in the metal oxide. 48 Similarly, we observed 12% Ce 3+ (XPS data) in the ultrathin CeO 2 surface, which forms oxygen defect sites leading to more surface adsorbed oxygen resulting in high NO 2 sensitivity.…”
Section: Resultssupporting
confidence: 60%
“…Ciftyurek et al reported exceptionally high gas sensing characteristics due to oxygen gas rapidly adsorbing on single and double-charged oxygen vacancy defect sites created by the presence of lower oxidation state of the metal in the metal oxide. 48 Similarly, we observed 12% Ce 3+ (XPS data) in the ultrathin CeO 2 surface, which forms oxygen defect sites leading to more surface adsorbed oxygen resulting in high NO 2 sensitivity.…”
Section: Resultssupporting
confidence: 60%
“…The types of surface ROS closely depend on the temperature. Molecular type O 2 – ions with relatively weak oxidizing capability are dominant below ∼150 °C (reaction 6), and atomic type O – ions with high oxidizing capability generally require high activation energy and become the primary species from ∼150 to 500 °C (via reaction 7). , Those ROS ions enable to oxidize the adsorbed DMDS molecules (via reactions 8–10) and donate electrons to the CuGaO 2 , resulting in an increase of sensor resistance (Figure ): 4 CH 3 SSCH 3 + 7 O 2 ( ads ) 4 CH 3 S + 4 CO 2 false( ad false) + 6 H 2 O + 7 e false( prefix< 150 ° normalC false) 2 CH 3 SSCH 3 + 7 O ( ads ) 2 CH 3 S + 2 CO 2 false( ad false) + 3 H 2 O ( ad ) + 7 …”
Section: Resultsmentioning
confidence: 99%
“…The peak area ratio of the adsorbed to hydroxyl species represents the oxygen vacancy states of the materials. 52,53 Their proportion can be calculated using the following eqs 4 and 5:…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Additionally, the intensity of oxygenated functional groups (with peak locations at 285.3, 286.2, and 288.8 eV) corresponds to C–O, CO, and plasmon π–π* transitions, respectively. , In Figure e,f, the O 1s XPS spectra is deconvoluted into two peaks belonging to the adsorbed and hydroxyl oxygen species on the surface of MWCNT and MWCNT-COOH. The peak area ratio of the adsorbed to hydroxyl species represents the oxygen vacancy states of the materials. , Their proportion can be calculated using the following eqs and : where A OH and A ads . are the integrated peak areas of the hydroxyl and adsorbed oxygen states, respectively.…”
Section: Resultsmentioning
confidence: 99%